Methodology of Teaching the Subject of Inter-Network Equilibrium Model (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This paper discusses the method of using the Maple software system when building a model of input-output balance. Using the capabilities of the Maple program to perform many calculations leads to good results. To date, a trained specialist is required to have competencies in the Maple program, which occupies one of the main places.